André Schaeffner et les origines corporelles de l’instrument de musique - Anne Boissière (Methodos, 2011)
Author of the classic study Origine des instruments de musique published in 1936, André Schaeffner (1895-1980) offers a reflection upon musical instruments which is a far cry from remaining within the confines of pure ethnology. Pondering the music of his own era, especially in the work of Stravinsky, as well as meditating over the origin of theatre and, following Nietzsche, over tragedy contributes to bringing about a conception of the instrument which cannot possibly be separated from a philosophy of music.  This article, as it explores the central topic of music’s « corporeal origins », presents three principal aspects in the light of which André Schaeffner is shown to thematize the status of the instrument as linked to the body sonorous and rhythmic : first, by rejecting any kind of voice-instrument dualism ; secondly, by refuting claims as to a supposedly manual origin of instruments, leading finally up to the idea of an organology of theatre.